Biochemical genetic markers in the Kadazans of Sabah, Malaysia. - Tan, Soon Guan; Teng, Yao Sheng; Ganesan, J.; Lau, K. Y.; Luang, Eng Lie-Injo (Springer, 1979)
Kadazans, the largest indigenous group in Sabah, northern Borneo, were surveyed for glyoxalase I, phosphoglucomutase I, red cell acid phosphatase, esterase D, adenosine deaminase, soluble glutamate pyruvate transaminase, soluble glutamate oxaloacetate transaminase, 6-phosphogluconate dehydrogenase, uridine monophosphate kinase, adenylate kinase, peptidase B and D, superoxide dismutase, C5, group specific component, haptoglobin and transferrin. Kadazans were found to be polymorphic for GLO I, PGM I, RCAP, esterase D, ADA, s-Gpt, 6PGD, UMPK, Gc, C5, haptoglobin and peptidase B. Rare variants were found for transferrin and peptidase D. No variant was found for s-Got, SOD and AK.